Asymmetric Information and the Market Structure of the Banking Industry - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 1998)
The paper analyzes the effects of informational asymmetries on the market structure of the banking industry in a multi-period model of spatial competition. All lenders face uncertainty with regard to borrowers' creditworthiness, but, in the process of lending, incumbent banks gather proprietary information about their clients, acquiring an advantage over potential entrants. These informational asymmetries are an important determinant of the industry structure and may represent a barrier to entry for new banks. The paper shows that, in contrast with traditional models of horizontal differentiation, the steady-state equilibrium is characterized by a finite number of banks even in the absence of fixed costs.